Student’s life in hostel during Covid-19 / Nur Syabrina Audra Amran, Nur Adriana Mohd Ruslan and Najaa Nazihah Mohd Badrol - Amran, Nur Syabrina Audra; Mohd Ruslan, Nur Adriana; Mohd Badrol, Najaa Nazihah (Faculty of Communication & Media Studies, 2021)
There is already emerging evidence to what is happening here in Malaysia. University students stranded at campuses nationwide have been told to stay put until the end of the MCO starting on March 18. This decision has caused students having depression and anxiety due to various factors, including living in isolation, not being able to see their families, worry about their families’ well-being, and concern on the impact of the lockdown on their study plans. There are good reasons to be concerned that prolonged isolation and separation from families will further adversely affect the mental health of students. It is not unexpected that parents would be worried about the well-being of children who are stranded on campus. For the methodology of this research, the researchers follow the research design of qualitative research. The researchers uses semi-structured interview in gathering information from the informants. One student from Universiti Utara Malaysia, one from UiTM Seri Iskandar, one from UiTM Perlis, two from UiTM Alor Gajah and two from UiTM Kuantan were interviewed. At the end, the researchers found out that most of the students are not happy with the news that they were not able to go back home for months and need to stay in their hostels during the pandemic of COVID-19 that begin to make them having mental breakdown and hard for them to live in the new norm.